Perlindungan Hukum Terhadap Pemegang Polis Asuransi Jiwa Pada PT FWD Life Indonesia Cabang Denpasar - Ida Ayu Ketut Sarwini; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
In everyday life humans are never free from the threat of disaster. This is where the importance of an insurance service as an investment. From the description of the background of the problem, the formulation of the problem in this study is How is the implementation of unit-linked life insurance at PT FWD Life Indonesia Denpasar Branch? What is the legal protection given to unit-link life insurance policy holders at PT FWD Life Indonesia Denpasar Branch? This type of research is a type of normative legal research. The source of legal material consists of primary legal material and secondary legal material. Methods of collecting legal materials using documentation and recording methods. Data analysis techniques use analytical techniques in a legal and descriptive interpretation. Conclusions from this study are unit-link life insurance implementation at PT FWD Life Indonesia Denpasar Branch conducted by fulfilling the requirements of Sales illustration and eSPAJ, Photo of identity card holder or main insured or insured, Complete account auto debit, Credit card auto debit, Signature confirmation form electronics and FNA (Financial Need Analysis) and RPO (Risk Profile Questionnaire) specifically for links in electronic form along with eSPAJ. Legal protection given to unit-link life insurance policy holders at PT FWD Life Indonesia Denpasar Branch is to fulfill the rights and obligations that should be owned by policy holders of PT FWD Life Indonesia Denpasar Branch and business people of PT FWD Life Indonesia Denpasar Branch. Legal protection can also be emphasized by providing compensation, resolving disputes and sanctions against companies that violate giving compensation to policy holders of PT FWD Life Indonesia Denpasar Branch